2016
DOI: 10.1371/journal.pone.0143837
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Admissions, Transfers and Costs of Guillain-Barré Syndrome

Abstract: BackgroundGuillain-Barré syndrome (GBS) has a highly variable clinical course, leading to frequent transfers within and between hospitals and high associated costs. We defined the current admissions, transfers and costs in relation to disease severity of GBS.MethodsDutch neurologists were requested to report patients diagnosed with GBS between November 2009 and November 2010. Information regarding clinical course and transfers was obtained via neurologists and general practitioners.Results87 GBS patients were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 20 publications
(26 reference statements)
0
8
3
1
Order By: Relevance
“…To fill this gap, there is a need for public health decision makers to assure the supply of intravenous immunoglobulin in the public health institutions network. This would likely reduce the need for transfers, which worsen GBS patient outcomes and are costly . We found that it is possible to predict the timing and location of hospitalizations with GBS with a statistical model using data on arbovirus cases.…”
Section: Discussionmentioning
confidence: 99%
“…To fill this gap, there is a need for public health decision makers to assure the supply of intravenous immunoglobulin in the public health institutions network. This would likely reduce the need for transfers, which worsen GBS patient outcomes and are costly . We found that it is possible to predict the timing and location of hospitalizations with GBS with a statistical model using data on arbovirus cases.…”
Section: Discussionmentioning
confidence: 99%
“…Despite recent progress in immunotherapy [37] , GBS remains a life-threatening condition, often requiring complex and expensive care [38] . Up to 20% of GBS cases result in severe disability, or even death [36] , while many other patients experience ongoing motor or sensory issues, fatigue and pain [39] .…”
Section: Zikv-mediated Pathogenesis?mentioning
confidence: 99%
“…Nonetheless, GBS is associated with substantial risks (including death) as well as financial costs for affected individuals [21] . Moreover, there are challenges with early GBS diagnosis, particular in atypical presentations and/or pediatric patients [38] . For example, cranial nerve enhancement -thought to be a part of GBS in pediatric patients [40] -was recently described from an imaging study of seemingly normal infant born after ZIKVpositive pregnancy.…”
Section: Zikv-mediated Pathogenesis?mentioning
confidence: 99%
“…К нередким внесуставным (системным) проявлениям воспалительных заболеваний суставов относятся различные поражения нервной системы, а в клиническом их течении важное значение имеет наличие и тяжесть периферической нейропатии (ПНП) [8], частота возникновения которой среди таких пациентов составляет 5-10 % [9,15]. Одним из вариантов ПНП при артритах является синдром Гийена -Барре (СГБ) [7], который обычно значительно ухудшает характер заболеваний [16], а с возрастом частота СГБ у пациентов растет [10]. Известны случаи возникновения СГБ при ревматоидном артрите (РА), хроническом хламидийном урогенитальном реактивном артрите (РеА), псориатическом артрите (ПА) и анкилозирующем спондилите (АС) на фоне лечения противоцитокиновыми препаратами, в частности ингибиторами туморонекротического фактора  [13,14,18].…”
Section: Introductionunclassified